2010
DOI: 10.1080/15438627.2011.534968
|View full text |Cite
|
Sign up to set email alerts
|

Step Time Variability and Pelvis Acceleration Patterns of Younger and Older Adults: Effects of Footwear and Surface Conditions

Abstract: This study investigated the effects of various shoe features and surfaces on step time variability and pelvis accelerations (RMS) during walking in six younger and 22 older adults. Participants walked at a self-selected speed in five shoe conditions (standard, elevated heel, soft sole, hard sole, and high collar) on two surfaces: level and irregular. Results showed an age-related reduction in step time variability on the irregular surface and increased medio-lateral (ML) acceleration RMS in older people walkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Similar to previous research [3,8,[10][11][12], we observed that younger people, non-fallers, and those without PD walk faster, and take longer steps, with reduced variability of step time. However, when we assessed these established gait parameters using univariant statistical analysis, we found substantial overlap between the distributions from different groups [18,19], which limits their utility as specific biomarkers at an individual level.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to previous research [3,8,[10][11][12], we observed that younger people, non-fallers, and those without PD walk faster, and take longer steps, with reduced variability of step time. However, when we assessed these established gait parameters using univariant statistical analysis, we found substantial overlap between the distributions from different groups [18,19], which limits their utility as specific biomarkers at an individual level.…”
Section: Discussionsupporting
confidence: 90%
“…Accelerometers have previously been connected to the head [3], pelvis [4], trunk [5,6], and even ski boots [7] to provide an inexpensive way to monitor human movement [8]. In clinical settings, accelerometers have been used to identify between-group differences in the gait of old and young [9,10], fallers and non-fallers [11], and people with and without Parkinson's disease (PD) [3,12]. Statistical associations, however, do not necessarily translate into biomarkers, if prevalence is low, as for PD, and falsepositive rates are high.…”
Section: Introductionmentioning
confidence: 99%
“…The research on turning that has been performed has been limited to laboratory or clinical investigations. Previous laboratory studies, with kinematics and surface electromyography, showed that young and older adults use different strategies during turning (19)(20)(21). Specifically, older adults, more than younger adults, reduce their walking speed and increase their step width just prior to the turn, suggesting a more cautious strategy (21).…”
mentioning
confidence: 95%
“…This finding suggests that a body’s dynamic balance ability is influenced by lower extremity muscle strength and is a crucial factor that prevents falling. Because stepping and walking entail the support of a single leg movement, aging causes reductions in lateral postural balance and subsequently results in the inability to maintain frontal plane balance [ 1 , 33 ]. Therefore, middle-age women should be conscious of performance decrease in lower extremity muscle strength to prepare for the influences induced by future aging.…”
Section: Discussionmentioning
confidence: 99%